Bilirubin Oxidation Products and Cerebral Vasoconstriction - Rapoport, Robert M. (Frontiers in Pharmacology, 2018)
Key evidence in support of the hypothesis that bilirubin oxidation products (BOPS) contribute to the vasoconstriction associated with subarachnoid hemorrhage (SAH) are the 1) presence of BOPS in cerebral spinal fluid (CSF) from SAH patients and 2) ability of one or more BOPS to elicit vasoconstriction. We critically evaluate this key evidence, detail where gaps remain, and describe recent approaches that will address these gaps.